Felder-Silverman Learning Style Model and the Relationship With Academic Performance - Dyah Lestari Widaningrum; Hwi Chie Ho (ANIMA Indonesian Psychological Journal, 2015)
The gap between organizational demands on employee competence and actual employee competence gives new challenges to the education industry to continually increase the readiness of its graduates. Teaching models are developed to produce graduates that are in accordance to the demands of the global competition. However in practice, educational staff often use the same model to all of their students (Blau, 2012), setting aside the importance of congruent concept in an effective pedagogical process (Akin-Little & Little, 2009). The current study is aimed to test the learning style of university engineering students based on the Felder-Silverman model and its role on academic performance. Results showed that engineering students in this study have the following learning style preferences: Active–Sensing–Visual–Global, which can be used as a base to design teaching methods, which will hopefully be able to provide better support to students‟ academic performance. Furthermore, a significant relationship between learning style for Active–Reflective dimension and academic performance was found, as indicated by their GPA.